SISTEM INFORMASI PENERIMAAN SISWA BARU (PSB) ONLINE PADA SMA NEGERI 2 TARUSAN DENGAN PHP DAN MYSQL - Andi, Tri; Nugraha, Hafiz (Jurnal EDik Informatika, 2020)
SMA Negeri 2 is Tarusan a secondary school in the Pesisir Selatan regency. Every new beginning academic year in the school, will be held the selection of new admissions. In the execution of these activities often face problems because the system used is still manual. With the New Student Reception Information System at SMAN 2 Online Tarusan expected to help deliver information and facilitate the execution of the processing and management of data for new students. The method uses in this research is interviewing, observation, literature study, analysis, system design, testing, and implementation. This research is expected of information systems created to provide the ease of implementation of a new student at SMAN 2 Tarusan.Keywords : Information Systems, Information Systems Admission.